Prasugrel in critically ill patients - Schoergenhofer, Christian; Hobl, Eva-Luise; Staudinger, Thomas; Speidl, Walter S.; Heinz, Gottfried; Siller-Matula, Jolanta; Zauner, Christian; Reiter, Birgit; Kubica, Jacek; Jilma, Bernd (Thrombosis and Haemostasis, 2017)
While prasugrel is indicated for the treatment of myocardial infarction, its effects in the most severely affected patients requiring intensive care is unknown, so that we measured the antiplatelet effects and sparse pharmacokinetics of prasugrel in critically ill patients. Twenty-three patients admitted to medical intensive care units, who were treated with 10 mg prasugrel once daily, were included in this prospective trial. Critically ill patients responded poorly to daily prasugrel treatment: adenosine diphosphate (ADP)-induced aggregation in whole blood classified 65 % (95 % confidence intervals (CI) 43–84 %) of patients as having high on treatment platelet reactivity, platelet function under high shear rates even 74 % (95 %CI 52–90 %). There was only limited additional inhibition provided 2 hours after the next dose of prasugrel. In contrast, insufficient inhibition of the target was only seen in 26 % (95 %CI 10–48 %) of patients as measured by the vasodilator-stimulated phosphoprotein phosphorylation (VASP-P) assay. Low effective plasma levels of prasugrel active metabolite were measured at trough [0.5 (quartiles 0.5–1.1) ng/ml at baseline], and 2 hours after intake [5.7 (3.8–9.8) ng/ml], but showed coefficients of variation of ~70 %. In sum, inhibition of platelet aggregation by prasugrel is not uniform but highly variable in critically ill patients, similar to clopidogrel in a general population. The pharmacokinetic measurements indicate that poor absorption/metabolism of prasugrel may partly contribute while inflammation induced heightened intrinsic platelet reactivity may also play a role.Supplementary Material to this article is available online at www.thrombosis-online.com.Note: This work was performed at the Medical University of Vienna, Austria.
Keywords: Antiplatelet drugs; intensive care unit; pharmacodynamics; pharmacokinetics; platelet function